(untitled) (Revista ABRA, 2007)
Expone los factores críticos que afectan las capacidades competitivas de las Mipymes y se indican los retos y dificultades. Explica las políticas de apoyo institucional que el Estado costarricense ha implementado y analiza los factores institucionales que han incidido en la neutralidad de la política pública de apoyo a las Mipymes. Sugiere recomendaciones para diseñar una política pública que fortalezca las capacidades competitivas de la Mipymes eficientemente. Abstract This paper analyses the relation between the competitiveness of small and medium size enterprises (SMEs) and the public policies framework. Specially, it explains the main policies that have been giving technical and financial support to SMEs in Costa Rica. Thus, institutions such as ministries have designed projects, programs and policies to solve internal and external requirements in term of technology, training, marketing, local infrastructure, credits, research and development, among others. However, small producers and manufactures criticize the labor and the efficiency of these institutions because they do not receive the all support that they need. Therefore, this paper suggests some recommendations to define a better policy framework to improve the competitiveness of SMEs in Costa Rica.